Electroacupuncture Ameliorates Mechanical Allodynia of a Rat Model of CRPS-I via Suppressing NLRP3 Inflammasome Activation in Spinal Cord Dorsal Horn Neurons - Zhang, Yunwen; Chen, Ruixiang; Hu, Qimiao; Wang, Jie; Nie, Huimin; Yin, Chengyu; Li, Yuanyuan; Wei, Huina; Liu, Boyu; Tai, Yan; Fang, Junfan; Shao, Xiaomei; et al. (Frontiers in Cellular Neuroscience, 2022)
Complex regional pain syndrome type-I (CRPS-I) is a chronic neurological disorder that results in severe pain and affects patients’ life quality. Conventional therapies usually lack effectiveness. Electroacupuncture (EA) is an effective physical therapy for relieving CRPS-I pain. However, the mechanism underlying EA-induced analgesia on CRPS-I still remain unknown. Spinal NLRP3 inflammasome was recently identified to contribute to pain and neuroinflammation in a rat model of CRPS-I by our group. In this study, we aimed to study whether EA could inhibit spinal NLRP3 inflammasome activation, thus resulting in pain relief and attenuation of spinal neuroinflammation in the rat model of CRPS-I. We established the rat chronic post-ischemic pain (CPIP) model to mimic CRPS-I. CPIP rats developed remarkable mechanical allodynia that could be relieved by daily EA intervention. NLRP3 inflammasome was activated in spinal cord dorsal horn (SCDH) of CPIP rats, accompanied with over-production of pro-inflammatory cytokine IL-1β. Immunostaining revealed that the cellular distribution of NLRP3 was predominantly located in SCDH neurons. Pharmacological activation of NLRP3 inflammasome per se is sufficient to produce persistent mechanical allodynia in naïve animals, whereas blocking NLRP3 inflammasome attenuates mechanical allodynia of CPIP rats. EA exclusively reduced NLRP3 overexpression in SCDH neurons and attenuated spinal glial cell over-activation in CPIP rats. EA-induced anti-allodynia, alongside with attenuation of spinal glial cell over-activation, were all mimicked by intrathecal blocking NLRP3 inflammasome and reversed by activating NLRP3 inflammasome, respectively, through pharmacological methods. Finally, spinal blocking IL-1β attenuated mechanical allodynia and spinal glial cell over-activation in CPIP rats, resembling the effects of EA. In all, these results demonstrate that spinal NLRP3 inflammasome activation contributes to mechanical allodynia of the rat model of CRPS-I and EA ameliorates mechanical allodynia through inhibiting NLRP3 inflammasome activation in SCDH neurons. Our study further supports EA can be used as an effective treatment for CRPS-I.